Nursing education in Turkey: From past to present - ALPAR, ŞULE (CHURCHILL LIVINGSTONE, 2009)
Nursing education in Turkey first began in 1912 with the introduction of a 6-month course to train voluntary medical attendants, with Dr. Besim Omer Pasha's advice to the Red Crescent Association regarding the inadequacy of healthcare services. as a crucial need for nursing services resulted due to significant losses given during Tripoli (1911) and the Balkan (1912) wars. Carrying out their duties in battlefields and hospitals with great devotion. the first nurses graduated from the course played a significant role in promoting the nursing profession and its importance. Nursing education which used to continue at the secondary and high-school levels increased to bachelor's level in 1955. Master's program in nursing was opened in 1968, and Ph.D. programs was opened in 1972. Professional members of the practice, well-equipped in accordance with the requirements of the age, who conduct their studies at the national and international levels, are trained as the consequence of the recent developments in nursing education. The number of nurses at the universities who offered higher levels of academic degree, and especially the number of nurses who gained 'science expert' title at the inpatient medical establishments has increased. This situation and globalization, which ensures an easier access to nursing literature through internet, enable a more systematic and of a better quality healthcare. This article explains the nursing education in Turkey from past to present. The developments in nursing education which have taken place in Turkey are expressed in a chronological order, starting from the Ottoman Empire, until the present. Compared with other countries, nursing education is given on different levels in Turkey. Recently, however, the obstacles regarding the differences especially at the bachelor's degree level were overcome, appropriate changes were made, and education melioration efforts gained speed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Nursing education; Nursing in Turkey